Pathologic rupture of the spleen in a patient with acute myelogenous leukemia and leukostasis - Santis,Gil Cunha De (2014)
Rupture of the spleen can be classified as spontaneous, traumatic, or pathologic. Pathologic rupture has been reported in infectious diseases such as infectious mononucleosis, and hematologic malignancies such as acute and chronic leukemias. Splenomegaly is considered the most relevant factor that predisposes to splenic rupture. A 66-year-old man with acute myeloid leukemia evolved from an unclassified myeloproliferative neoplasm, complaining of fatigue and mild upper left abdominal pain. He was pale and presented fever and tachypnea. Laboratory analyses showed hemoglobin 8.3 g/dL, white blood cell count 278 × 109/L, platelet count 367 × 109/L, activated partial thromboplastin time (aPTT) ratio 2.10, and international normalized ratio (INR) 1.60. A blood smear showed 62% of myeloblasts. The immunophenotype of the blasts was positive for CD117, HLA-DR, CD13, CD56, CD64, CD11c and CD14. Lactate dehydrogenase was 2384 U/L and creatinine 2.4 mg/dL (normal range: 0.7-1.6 mg/dL). Two sessions of leukapheresis were performed. At the end of the second session, the patient presented hemodynamic instability that culminated in circulatory shock and death. The post-mortem examination revealed infiltration of the vessels of the lungs, heart, and liver, and massive infiltration of the spleen by leukemic blasts. Blood volume in the peritoneal cavity was 500 mL. Acute leukemia is a rare cause of splenic rupture. Male gender, old age and splenomegaly are factors associated with this condition. As the patient had leukostasis, we hypothesize that this, associated with other factors such as lung and heart leukemic infiltration, had a role in inducing splenic rupture. Finally, we do not believe that leukapheresis in itself contributed to splenic rupture, as it is essentially atraumatic.